1990
DOI: 10.1289/ehp.9086107
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of a cohort of workers in the styrene-butadiene polymer manufacturing industry (1943-1982).

Abstract: A cohort of 12,110 male workers employed 1 or more years in eight styrene-butadiene polymer (SBR) manufacturing plants in the United States and Canada has been followed for mortality over a 40-year period, 1943 to 1982. The all-cause mortality of these workers was low [standardized mortality ratio (SMR) = 0.81] compared to that of the general population. However, some specific sites of cancers had SMRs that exceeded 1.00. These sites were then examined by major work divisions. The sites of interest included le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
4

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(32 citation statements)
references
References 6 publications
2
26
0
4
Order By: Relevance
“…Individuals with the GSTT1 null genotype (GSTT1 À ) have reduced ability to detoxify metabolites of 1, 3-butadiene and ethylene oxide [12,13] and people with the GSTM1 null (GSTM1 À ) genotype have reduced ability to detoxify metabolites of polycylic aromatic hydrocarbons such as benzo(a)pyrene [14]. In epidemiological studies, an association has been found between exposure to 1,3-butadiene and benzo(a)pyrene and lymphatic and hematopoietic cancers other than CML [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with the GSTT1 null genotype (GSTT1 À ) have reduced ability to detoxify metabolites of 1, 3-butadiene and ethylene oxide [12,13] and people with the GSTM1 null (GSTM1 À ) genotype have reduced ability to detoxify metabolites of polycylic aromatic hydrocarbons such as benzo(a)pyrene [14]. In epidemiological studies, an association has been found between exposure to 1,3-butadiene and benzo(a)pyrene and lymphatic and hematopoietic cancers other than CML [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In the most sensitive study, Matanoski et al (1990) reported that in a cohort of 12,110 male workers involved in styrene-butadiene polymer production, deaths from lymphopoietic cancers occurred slightly more frequently than expected compared to the U.S. general population. These results were based on 19 observed cases, 6 of which occurred in black production workers, a subgroup in which the excess was significant.…”
Section: Irritation Prenarcotic Symptoms and Altered Coordination Hmentioning
confidence: 95%
“…Volunteers exposed to a very high level of 8000 ppm of butadiene in air complained of eye irritation, blurring of vision, coughing, nasal congestion, and drowsiness. Subsequent repeated exposures did not suggest any cumulative effect [99,111].…”
Section: Human Datamentioning
confidence: 99%